Sound Properties Investigation of Date Palm Fiber. (January 2019) - Mohammad, M.; Nik Syukri, N.I.R.; Nuawi, M.Z.
Abstract: This research is carried out to determine the sound absorption coefficient (α) and noise reduction coefficient (NCR) of date palm fibre. The specimen made of date palm fibre has been compressed using certain weight to maintain desire thickness range from 10 mm to 50 mm. The specimen has been mixed with coconut fibre at a certain ratio. Experiment had been conducted using impedance tube to determine the sound absorption coefficient values follows ISO 10534-2:1998 standard procedure. Single value of coefficient had been calculated based on ASTM 423. Result showed that thicker specimen having higher value of α and NCR. Specimen with mixing ratio of 75% and 50 mm thickness have shown the highest NCR value of 0.6 compared other specimens. NCR comparison with domestic glass fiber used in the construction industries shows that this material has very good potential to be developed as one of the sound absorption component in related industry.